(untitled) (Research Nepal Journal of Development Studies, 2019)
Roles of Rahul Sankrityayan in Nepalese Cultural Tourism are an analysis of Nepalese Cultural tourism potentialities and facilitation of great personality. The study has identified the points on Independent Movement, on Diplomacy, on Buddhist Religious Tourism, on Art, Literature, and Language, and on Theorizing Tourism. Therefore, Nepal has to make a park in the memory of Sankrityayan with a Vihar for meditation, museum and library for the researchers and Stupa with some sorts of relics pilgrims. The main objective of the study is to find out the contributions of Sankrityayan in Nepalese Tourism development and to identify the roles of Rahul in cultural tourism in between India and Nepal. Methodologically the study is a general literature review of secondary information to identify and describe the roles of Rahul on the development of Nepalese Cultural Tourism. Every Indian Buddhist, Vaishnava, Marxist, or Student visitors to Nepal are compelled to visit and homage the tribute to Rahul. This compulsion really takes place in the cultural tourism development of both the countries and strengthens the diplomatic tie in people to people connectivity.